The Influence of Limited Time Scarcity and Limited Quantity Scarcity on Impulsive Buying Behavior: Evidence from Somethinc × Batman Limited Edition Consumers on Shopee - Aminah Akhazati Nur; Iwan Sukoco; Raden Marsha Aulia Hakim (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The growing adoption of e-commerce in Indonesia has encouraged beauty brands to leverage scarcity-based marketing strategies, through both time-limited and quantity-limited promotions, to drive sales on digital platforms. However, which dimension of scarcity more powerfully triggers impulsive purchasing behavior, particularly for limited-edition collaboration products, has not been specifically examined. This study aims to analyze the effect of Limited Time Scarcity (LTS) and Limited Quantity Scarcity (LQS) on Impulsive Buying among consumers of the Somethinc x Batman product on Shopee, both partially and simultaneously. A quantitative research method was employed using a survey with a 5-point Likert scale questionnaire administered to 135 respondents residing in Bandung who had previously purchased the product through Shopee. Data were analyzed using multiple linear regression following validity, reliability, normality, multicollinearity, and heteroscedasticity tests. The results show that LTS has a positive and significant effect on Impulsive Buying (t = 13.043) with a partial contribution of 50%, while LQS also has a positive and significant effect (t = 6.894) with a partial contribution of 18%. Simultaneously, both variables significantly affect Impulsive Buying (F = 147.802; R² = 0.691). This study concludes that LTS is the dominant dimension of scarcity in driving Impulsive Buying among consumers of limited-edition collaboration products on e-commerce platforms, with an influence nearly three times greater than LQS.